Prevalence of dental caries based on gender at Puskesmas Kerambitan II, Tabanan Bali, during the period October 2024-March 2025: Prevalensi karies gigi berdasarkan jenis kelamin di Puskesmas Kerambitan II periode Oktober 2024-Maret 2025 Tabanan Bali - Pradnyanandini, Made Ayu Imas; Pratama, I Wayan Agus Wirya; Suryani, Ni Putu Ary Wahyu (Makassar Dental Journal, 2025)
Public awareness of the importance of dental health remains low. Based on registration data at the Kerambitan II Community Health Centre for the period October 2024 to March 2025, dentine caries ranked fourth among the ten most common diseases at the clinic. A descriptive study in the form of an epidemiological case report covering six months from October 2024 to March 2025 was conducted in April 2025 at the Kerambitan II Community Health Centre. The population consisted of all patients who had their teeth and mouth examined at the Dental Clinic, and the sample consisted of all patients suffering from caries. The prevalence of dental caries between males and females showed that dental caries was more common in females. The highest number was in October 2024, with 13 females (61.90%). It was concluded that based on gender, dental caries was more common in females.